An Ethical Dilemma in SARS-Cov-2 Pandemic : Who Gets the Ventilator? - Raluca, Dumache; Veronica, Ciocan; Oana, Muresan Camelia; Alexandra, Enache (European Scientific Journal, ESJ, 2020)
Since the current pandemic is an emergency situation worldwide, there’s a shortage of mechanical ventilators, intensive care unit (ICU) beds, and other medical equipment. Due to new disease and insufficient medical data, it is difficult to ensure access to life-saving treatments for people with various vulnerabilities. From an ethical point of view, the current guidelines and recommendations, as incomplete as they are, suggest the utilitarian principle that the allocation of life-saving treatments is based on assessing patients' chances of survival.